RANCANG BANGUN MESIN PENEKUK PLAT DENGAN SISTEM HIDROLIK TEBAL PLAT 4 MM - Bambang Pratowo; Witoni Witoni; Prasetyo Prasetyo (Universitas Bandar Lampung, 2021)
Hydraulik bending machine is a tool that is used for the process of forming the plate by bending the workpiece so that in undergoes a (deformation) that causes plate tension around the neutral area. Using a hydraulic system can bend the plate in a way that is easier and more efficient and more precies. The method of making hydraulic bending tools includes planning, then the production process and testing tools. The hydraulic system with a starting drive to power the electric motor 1 HP at 1420 rpm produces a directional control valve trough the pushbutton. Directional control valve function to regulate fluid to actuator. Plate bending process with a maximum thickness of 4 mm, a length of 350 mm stretch.